2017
DOI: 10.1016/j.jpeds.2016.09.063
|View full text |Cite
|
Sign up to set email alerts
|

Applying Cystic Fibrosis Transmembrane Conductance Regulator Genetics and CFTR2 Data to Facilitate Diagnoses

Abstract: The use of CFTR genetics to aid in diagnosis of CF requires that the mutations identified have a known disease liability. The demonstration of 2 in trans mutations known to always result in CF is satisfactory evidence of CFTR dysfunction. However, if the identified mutations are known to be associated with variable outcomes, or have unknown consequence, that genotype may not result in a CF phenotype. In these cases, other tests of CFTR function may help.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 30 publications
1
48
0
1
Order By: Relevance
“…First and foremost, it is recommended as essential that diagnoses of disorders associated with CFTR mutations be established in all individuals from newborn to adult by evaluation of CFTR function with a sweat chloride test or, if this is not possible, another established test of chloride channel functioning as described herein by Farrell et al 13 and Ren et al 17 Newborn infants with a high level of immunoreactive trypsinogen and inconclusive CFTR functional and genetic testing may be designated either CRMS or CFSPID; these 2 terms are now merged and equivalent, so that CRMS/CFSPID may be used as was done recently by Castellani et al 18 The committee also recommends that the latest mutation classifications annotated in the CFTR2 project 19 should be used to aid in CF diagnosis. Finally, as described in the Supplement article on genetic aspects by Sosnay et al, 12 all patients with CF should be genotyped, even if the diagnosis was confirmed with sweat test results and/or they had DNA analyses as part of NBS.…”
Section: Supplementmentioning
confidence: 99%
See 1 more Smart Citation
“…First and foremost, it is recommended as essential that diagnoses of disorders associated with CFTR mutations be established in all individuals from newborn to adult by evaluation of CFTR function with a sweat chloride test or, if this is not possible, another established test of chloride channel functioning as described herein by Farrell et al 13 and Ren et al 17 Newborn infants with a high level of immunoreactive trypsinogen and inconclusive CFTR functional and genetic testing may be designated either CRMS or CFSPID; these 2 terms are now merged and equivalent, so that CRMS/CFSPID may be used as was done recently by Castellani et al 18 The committee also recommends that the latest mutation classifications annotated in the CFTR2 project 19 should be used to aid in CF diagnosis. Finally, as described in the Supplement article on genetic aspects by Sosnay et al, 12 all patients with CF should be genotyped, even if the diagnosis was confirmed with sweat test results and/or they had DNA analyses as part of NBS.…”
Section: Supplementmentioning
confidence: 99%
“…International collection of clinical data from individuals with CF and recent laboratory advances [8][9][10][11] have provided new insights into the physiological impact of the most common mutations. 12,13 Because of this new information, and to seek harmony with the diagnostic criteria and terminology 14 of the European CF Society (ECFS), it was decided that the diagnostic guidelines of the CF Foundation 4 published in 2008 should be revised.…”
mentioning
confidence: 99%
“…The identification of two disease-causing mutations allows a presumptive diagnosis; however, a sweat test is still required to confirm the diagnosis. 8,93,94 Disadvantages are the cost, the complexity, and the inadvertent identification of CF carriers, and of infants in whom the diagnosis is uncertain. 9,46,95 There are variations to the IRT/DNA model.…”
Section: Improving Specificity With Second-tier Testingmentioning
confidence: 99%
“…8,93,94 It is sometimes suggested that it is unnecessary in infants with two disease causing mutations identified; however, there remain strong arguments to confirm this life-long condition, with significant morbidity and mortality, with a physiological test demonstrating CFTR dysfunction. 8,68,93,108,109 Sweat testing infants at this age are challenging. Guidelines suggest it should be possible to collect sweat from infants over 36-weeks corrected gestational age and >2-kg weight.…”
Section: Sweat Testing As a Part Of Cf Nbsmentioning
confidence: 99%
“…CF is an autosomal recessive disease occurring when an individual possesses mutations on both alleles of the gene encoding the cystic fibrosis transmembrane conductance regulator (CFTR) protein; within this large gene, there are numerous disease-causing mutations (2). Normal CFTR is required for homeostasis of the airway surface liquid and mucus, through roles in chloride, sodium and bicarbonate secretion.…”
Section: Understanding the Link Between Lack Of Cftr Function And Cf mentioning
confidence: 99%